2017
DOI: 10.1016/j.scr.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Murine pluripotent stem cells with a homozygous knockout of Foxg1 show reduced differentiation towards cortical progenitors in vitro

Abstract: Foxg1 is a transcription factor critical for the development of the mammalian telencephalon. Foxg1 controls the proliferation of dorsal telencephalon progenitors and the specification of the ventral telencephalon. Homozygous knockout of Foxg1 in mice leads to severe microcephaly, attributed to premature differentiation of telencephalic progenitors, mainly of cortical progenitors. Here, we analyzed the influence of a Foxg1 knockout on differentiation of murine pluripotent stem cells (mPSCs) in an in vitro model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Mutations in FOXG1 are causal of a rare neurodevelopmental disorder (FOXG1 syndrome) that results in abnormal brain function. Studies showed that complete loss of foxg1 in mice is post-natally lethal, while homozygous knockout of the gene in differentiating cells leads to generation of significantly smaller embryoid bodies ( Martynoga et al, 2005 ; Mall et al, 2017 ; Hettige et al, 2019 ). It has been shown that during early brain development, FOXG1 can directly control levels of PAX6 and inhibit the premature differentiation of neurons ( Manuel et al, 2011 ; Patriarchi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in FOXG1 are causal of a rare neurodevelopmental disorder (FOXG1 syndrome) that results in abnormal brain function. Studies showed that complete loss of foxg1 in mice is post-natally lethal, while homozygous knockout of the gene in differentiating cells leads to generation of significantly smaller embryoid bodies ( Martynoga et al, 2005 ; Mall et al, 2017 ; Hettige et al, 2019 ). It has been shown that during early brain development, FOXG1 can directly control levels of PAX6 and inhibit the premature differentiation of neurons ( Manuel et al, 2011 ; Patriarchi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…[168][169][170] Cortical neurons generated from FOXG1deficient mouse pluripotent stem cells express reduced level of vGluTt1. 171 Similarly, patient-derived iPSCs and from mice hemizygous for FOXG1 deletion display reduced vGlut1. 172 With regard to astrocytes-expressing MeCP2 in MeCP2lacking astrocytes results in the elevation of vGlut1 in MeCP2-deficient neurons and restoration of normal dendritic morphology.…”
Section: Potential Common Effectorsmentioning
confidence: 99%
“…168170 Cortical neurons generated from FOXG1-deficient mouse pluripotent stem cells express reduced level of vGluTt1. 171 Similarly, patient-derived iPSCs and from mice hemizygous for FOXG1 deletion display reduced vGlut1. 172…”
Section: Potential Common Effectorsmentioning
confidence: 99%
“…Other models of complete loss of Foxg1 have also been investigated. In a homozygous knockout neuronal cell line, embryoid bodies (EBs) derived from induced pluripotent stem cells (iPSCs) were significantly smaller (88), supporting a role for Foxg1 in cell survival. In vivo adult neurogenesis models support this finding.…”
Section: Foxg1 Dose and Cell Survivalmentioning
confidence: 99%